The impact of a shift in organizational role on ethical perceptions: A comparative study - Kaynama, Shohreh A. (Journal of business ethics, 1996)
This study investigates ethical decision-making by considering the differences in ethical judgments between undergraduate business and MBA students on selected ethical issues facing employees and managers of today's businesses. The study further investigates differences in ethical judgments between undergraduates and MBAs in terms of a perceived position as an employee or as a manager. The findings indicate that undergraduate students tend to be more ethical than MBA students and that both groups tend to be more ethical when they perceive themselves as managers rather than employees. The authors discuss the implications for both business practitioners and educators.